2018
DOI: 10.15294/dp.v13i2.16852
|View full text |Cite
|
Sign up to set email alerts
|

Learning Community on Computer-Based Statistics Acceptance for Accounting Students

Abstract: This study aims to examine the influence of the learning community on computer-based statistic acceptance. Acceptability is measured with perceived usefulness variables, perceived ease of use, perceived enjoyment, and reuse intention. This study used quasi-experimental design. To selecting the respondents, researchers used cluster random sampling and a questionnaire to collect the data. Respondents consisted of 207 accounting students of which 86 were engaged in the learning community while 121 were not. One-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…After completion of the internship, students will obtain a certificate of technical competence and a certificate of apprenticeship accounting of the industry. Overall the above research results are in line with the research of Hafsah, Sagala & Ramdhansyah (2018) which suggests that to achieve graduates who are proficient in analysis and interpretation, universities need to improve the existing formal and informal learning processes.…”
Section: Application Of Model Internshipsupporting
confidence: 85%
“…After completion of the internship, students will obtain a certificate of technical competence and a certificate of apprenticeship accounting of the industry. Overall the above research results are in line with the research of Hafsah, Sagala & Ramdhansyah (2018) which suggests that to achieve graduates who are proficient in analysis and interpretation, universities need to improve the existing formal and informal learning processes.…”
Section: Application Of Model Internshipsupporting
confidence: 85%
“…Simultaneously, many practical aspects and implications that need to be further discussed are related to developing student competencies, for example, in the use of data analysis software in conducting quantitative studies. To support the classroom's learning process, students need to strengthen knowledge outside the classroom through directed discussion with their colleagues to complete assignments, projects, mini research, and so on (Hafsah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of this community has been widely developed in knowledge management (Dalkir, 2013). Research of Hafsah et al, (2018) and Hasibuan et al, (2020) have also revealed that the learning community has a significant impact on academic performance and student capabilities mastering computerbased statistics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations